Menopausal hormone therapy: a systematic review of cost-effectiveness evaluations - Louiza S. Velentzis; Usha Salagame; Karen Canfell (BMC, 2017)
Abstract Background Several evaluations of the cost-effectiveness (CE) of menopausal hormone therapy (MHT) have been reported. The aim of this study was to systematically a﻿nd critically review economic evaluations of MHT since 2002, after the Women's Health Initiative (WHI) trial results on MHT were published. Methods The inclusion criteria for the review were: CE analyses of MHT versus no treatment, published from 2002-2016, in healthy women, which included both symptom relief outcomes and a range of longer term health outcomes (breast cancer, coronary heart disease, stroke, fractures and colorectal cancer). Included economic models had outcomes expressed in cost per quality-adjusted life year or cost per life year saved. MEDLINE, EMBASE, Evidence-Based Medicine Reviews databases and the Cost-Effectiveness Analysis Registry were searched. CE evaluations were assessed in regard to (i) reporting standards using the CHEERS checklist and Drummond checklist; (ii) data sources for the utility of MHT with respect to menopausal symptom relief; (iii) cost derivation; (iv) outcomes considered in the models; and (v) the comprehensiveness of the models with respect to factors related to MHT use that impact long term outcomes, using breast cancer as an example outcome. Results Five studies satisfying the inclusion criteria﻿ were identified which modelled cohorts of women aged 50 and older who used combination or estrogen-only MHT for 5-15 years. For women 50-60 years of age, all evaluations found MHT to be cost-effective and below the willingness-to-pay threshold of the country for which the analysis was conducted. However, 3 analyses based the quality of life (QOL) benefit for symptom relief on one small primary study. Examination of costing methods identified a need for further clarity in the methodology used to aggregate costs from sources. Using breast cancer as an example outcome, risks as measured in the WHI were used in the majority of evaluations. Apart from the type and duration of MHT use, other effect modifiers ﻿for breast cancer outcomes (for example body mass index) ﻿were not considered. Conclusions This systematic review identified issues which could impact the outcome of MHT CE analyses and the generalisability of their results. The estimated CE of MHT is driven largely by estimates of QOL improvements associated with symptom relief but data sources on these utility weights are limited. Future analyses should carefully consider data sources and the evidence on the long term risks of MHT use in terms of chronic disease. Th﻿is review ﻿highlights the considerable ﻿difficulties in conducting cost-effectiveness analyses in situations where short term benefits of an intervention must be evaluated in the context of long term health outcomes.